1826 – 1828 ԹԹ. Ռուս - պարսկական պատերազմին մասնակցած հայկական աշխարհազորային դրուժինաների հաստիքակազմը, թվակազմը, համազգեստը, սպառազինությունը և մարտական դրոշներ - Նազարյան, Հայկ (Հայաստանի պատմության թանգարան)
During the Russo-Persian War (1826 – 1828) Armenian Volunteer Detachments were organized and three Militia Druzhinas were formed. The main organizer of this process was the spiritual leader of Armenians in Georgia, Archbishop Nerses. The three Armenian Militia Druzhinas passed a brilliant martial way. They took part at the main battles of the war and liberated the strategic fortresses. As a result they had their great contribution in the victory of Russian Army and the liberation of Eastern Armenia from the Persian yoke. Во время русско-персидской войны 1826 – 1828 гг. было создано несколько армянских добровольческих отрядов, а, по инициативе Главы Грузино-Имеретинской армянской епархии архиепископа Нерсеса, сформированы три армянские ополченческие дружины. Ополченческие дружины прошли блестящий боевой путь, принимая участие в главных сражениях войны и освобождении крепостей стратегического назначения, тем самым внесли большой вклад в победу Русской армии в этой войне и освобождении Восточной Армении от персидского ига.
Keywords: Պատմություն